Project scheduling with discrete time-resource and resource-resource tradeoffs - Arno Sprecher; Sönke Hartmann; Andreas Drexl (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1994)
We consider an extension of the classical resource-constrained project scheduling problem (RCPSP), which covers discrete resource-resource and time-resource tradeoffs. As a result a project scheduler is permitted to identify several alternatives or modes of accomplishment for each activity of the project. The solution procedure we present is a considerable generalization of the branch-and-bound algorithm proposed by Demeulemeester and Herroelen, which is currently the most powerful method for optimally solving the RCPSP. More precisely, we extend their concept of delay alternatives by introducing mode alternatives. The basic enumeration scheme is then enhanced by dominance rules which highly increase the performance of the algorithm. The computational results obtained by solving the Standard ProGen instances indicate that the new method outperforms the most rapid procedure reported in the literature by a factor of four. Additionally and more important than the average reduction of the solution time is the substantial decrease of the variance of the solution times.
Keywords: 650; Project Management / Scheduling; Discrete Resource-Resource / Time-Resource Tradeoffs; Delay and Mode Alternatives; Branch-and-Bound; Dominance Rules; Computational Results; Projektmanagement; Mathematische Optimierung; Theorie